Growth of horizontally aligned carbon nanotubes - Chee, Kin Onn. (2011)
Since its introduction in the early 1990s, carbon nanotubes (CNTs) have been widely investigated for their unique structure and properties which qualifies their importance for a huge variety of electrical and mechanical applications. Among the three main synthesis methods for carbon nanotubes, chemical vapor deposition (CVD) has been most widely discussed and adopted, and which was used in the experiment for this project.